Analysis of SMEs in Hungary compared with Romania using the information and communications technology in this sector - NĂFTĂNĂILĂ, Cristina Alina (Annals of Spiru Haret University. Economic Series, 2011)
Small and medium enterprises contribute greatly to achieving the fundamental objectives of any national economy. They play an important role in the economy for reasons such as: foster innovation and flexibility; they can be integrated relatively easily into a regional industrial network, which contributes to the economic development in the region, reducing unemployment and raising the living standards because it provides jobs, stimulate competition, helps the functioning of large companies that provide different services or producing different parts. In this article I made a comparison of small and medium enterprise sector in Hungary and Romania.